Mitochondrial VDAC2 and cell homeostasis: highlighting hidden structural features and unique functionalities. (7th November 2016) - Maurya, Svetlana Rajkumar; Mahalakshmi, Radhakrishnan
ABSTRACT: Voltage‐dependent anion channels (VDACs) are the gateway to mitochondrial processes, interlinking the cytosolic and mitochondrial compartments. The mitochondrion acts as a storehouse for cytochrome c, the effector of apoptosis, and hence VDACs become intricately involved in the apoptotic pathway. Isoform 1 of VDAC is abundant in the outer mitochondrial membrane of many cell types, while isoform 2 is the preferred channel in specialized cells including brain and some cancer cells. The primary role of VDACs is metabolite flux. The pro‐ and anti‐apoptotic role of VDAC1 and VDAC2, respectively, are secondary, and are influenced by external factors and interacting proteins. Herein, we focus on the less‐studied VDAC2, and shed light on its unique functions and features. VDAC2, along with sharing many of its functions with VDAC1, such as metabolite and Ca 2+ transport, also has many delineating functions. VDAC2 is closely engaged in the gametogenesis and steroidogenesis pathways and in protection from oxidative stress as well as in neurodegenerative diseases like Alzheimer's and epilepsy. A closer examination of the functional pathways of VDACs indicates that the unique functions of VDAC2 are a result of the different interactome of this isoform. We couple functional differences to the structural and biophysical evidence obtained for the VDACs, and present a testament of why the two VDAC isoforms with >90% sequence similarity, are functionally diverse. Based on these differences, we suggest that the VDAC isoforms now be considered as paralogs. An in‐depth understanding of VDAC2 will help us to design better biomolecule targets for cancer and neurodegenerative diseases.